1978
DOI: 10.1073/pnas.75.8.3722
|View full text |Cite
|
Sign up to set email alerts
|

Purine metabolism in cultured human fibroblasts derived from patients deficient in hypoxanthine phosphoribosyltransferase, purine nucleoside phosphorylase, or adenosine deaminase.

Abstract: ABS14RACT Rates of purine synthesis de novo, as measured by the incorporation of [4C]formate into newly synthesized purines, have been determined in cultured human fibroblasts derived from normal individuals and from patients deficient in adenosine deaminase, purine nucleoside phosporylase, or hypoxanthine phosphoribosyltransferase, three consecutive enzymes of the purnne salvage pathway. All four types of cell lines are capable of incorporating [14C]formate into purines at approximately the same rate when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Thus, our studies overall are quite compatible with data from other cells, which suggest that the cellular content of NTP is modulated by two interactive variables-the negative feedback control of nucleotides upon their own synthesis (at several enzymatic levels; references 11, 24,31,[55][56][57][58] and positive regulatory control by PRPP (27,38,41,56). Possible site(s) ofaction ofglucose on nucleotide synthesis.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Thus, our studies overall are quite compatible with data from other cells, which suggest that the cellular content of NTP is modulated by two interactive variables-the negative feedback control of nucleotides upon their own synthesis (at several enzymatic levels; references 11, 24,31,[55][56][57][58] and positive regulatory control by PRPP (27,38,41,56). Possible site(s) ofaction ofglucose on nucleotide synthesis.…”
Section: Discussionsupporting
confidence: 77%
“…The rise in GTP (and in insulin secretion) induced by guanine, and the fall in both parameters induced by MPA, were in general, inversely proportional to the starting content ofpurine nucleotides, which are feedback inhibitors of salvage ( 11 ) and de novo ( 1 1, 31, 55 ) synthetic pathways as well as ofthe synthesis of their common precursor PRPP (1 1,24,41,[55][56][57]. Thus, our studies overall are quite compatible with data from other cells, which suggest that the cellular content of NTP is modulated by two interactive variables-the negative feedback control of nucleotides upon their own synthesis (at several enzymatic levels; references 11, 24,31,[55][56][57][58] and positive regulatory control by PRPP (27,38,41,56).…”
Section: Discussionmentioning
confidence: 99%
“…Obligate intracellular pathogens as diverse as viruses and the eukaryotic pathogens Plasmodium falciparum and microsporidia depend on their hosts for purines, with several types of transporters identified in eukaryotic pathogens used to steal purines from hosts [46, 4446]. Extensive work on purine metabolism and its effects on human physiology have come from studies of so-called ‘inborn errors of metabolism’, which are often due to mutations in purine enzymes [21, 38, 4750]. Interestingly, although mutations in enzymes of the purine de novo and salvage pathways cause of various disorders (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In this latter case, any metabolic determinations reflect the total cell population and not just the target cells. Previous work indicated that there is a close correlation between host cell nucleic acid metabolism and the ability of M. pneumoniae to cause a cytopathic effect (CPE) in host cells (24). In this study, we used normal human lung fibroblasts (MRC-5 cells) and Lesch-Nyhan fibroblasts, which are deficient in hypoxanthine-guanine phosphoribosyl transferase (HGPRT; EC 2.4.2.8), to probe the effects of M. pneumoniae infection further (15,23,27). As the Lesch-Nyhan cells are HGPRT deficient, they lack the purine salvage pathway.…”
mentioning
confidence: 99%